The preventive effect of phenolic-rich extracts from Chinese sumac fruits against nonalcoholic fatty liver disease in rats induced by a high-fat diet. Issue 1 (13th January 2020) - Wu, Zihuan; Zhang, Yan; Gong, Xiarong; Cheng, Guiguang; Pu, Shibiao; Cai, Shengbao
Abstract : The objective of this study is to investigate the preventive effect of phenolic-rich extracts from Chinese sumac ( Rhus chinensis Mill.) fruits against NAFLD in rats induced by a high-fat diet and to clarify the underlying mechanisms. Abstract : The objective of this study is to investigate the preventive effect of phenolic-rich extracts from Chinese sumac ( Rhus chinensis Mill.) fruits against nonalcoholic fatty liver disease (NAFLD) in rats induced by a high-fat diet and to clarify the underlying mechanisms. The results showed that the phenolic-rich extract remarkably improved some critical biochemical indexes, including TG, TC, MDA, ALT, AST, and endogenous antioxidant enzymes. The results of immunofluorescence and TUNEL assay showed that the extract obviously reduced the level of NF-κB in cell nuclei and suppressed hepatocyte apoptosis. Moreover, immunohistochemistry and western blot analyses further revealed that the phenolic-rich extract can improve NAFLD in high-fat diet induced rats by regulating several key proteins related to lipid metabolism, inflammation and apoptosis of hepatocytes, namely upregulating the expression levels of p-AMPK, PPAR-α, CPT1 and Bcl-2, and downregulating the levels of PPAR-γ, CYP2E1, p-P38, p-NF-κB, iNOS, COX-2, caspase-3D and Bax. These results indicate that the phenolic-rich extract from Chinese sumac fruits could prevent NAFLD in rats by regulating some critical proteins in several signalling pathways and may be provided as a new natural ingredient for developing functional foods and/or nutraceuticals to prevent NAFLD.